A composite steel slag activator modified steel slag material and preparation method thereof
By adding a prepared corrosion -resistant enhancer in the composite steel residue excitation agent, the problem of the use of the medium alkali collection material in the use of the metaphysical alkali material was solved, and the alkali resistance of the steel residue material was improved and the pressure resistance was improved.
Patent Information
- Application Number
- CN202411389893.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-08
AI Technical Summary
During use, existing steel slag excitants are prone to cause alkali aggregate reactions, resulting in changes in the steel slag structure and volume, reduced durability and strength, and cannot be repaired.
By preparing a corrosion-resistant enhancer and adding it to the composite steel slag activator, the alkali resistance of the steel slag is improved and the alkali aggregate reaction is avoided. The corrosion resistance enhancer consists of 4-amino-1,8-naphthalenedicarboxylic anhydride, ammonium thiocyanate, concentrated sulfuric acid, hydrogen bromide, trifluoroacetyl chloride, triethylamine, tetrabutylammonium bromide and 2,2 , 2-trifluoroethylamine and other raw materials are made through multi-step reactions and have good thermal stability and alkali resistance.
The alkali resistance of the steel residue agent is achieved, the alkaline collection reaction is avoided, the pressure and stability of the steel residue material is improved, and the long -term stability and use effect of the material are ensured.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of industrial admixtures, and in particular relates to a composite steel slag activator modified steel slag material and a preparation method thereof. Background Art
[0002] Steel slag is a solid waste generated during the steel production process, which contains a large amount of metal oxides, silicate minerals and other inorganic compounds. Steel slag activator is a process admixture that can promote the activation and reuse of mineral components in steel slag. It mainly reacts chemically with the mineral components in steel slag to generate hydrated products with gelling properties (such as hydrated calcium silicate, hydrated calcium aluminate, etc.), thereby improving the strength and activity of steel slag. Using steel slag activator to activate steel slag is an effective means of treating steel slag in the prior art.
[0003] At present, steel slag activators mainly include alkaline activators and salt activators, among which alkaline activators have the best activating effect. However, excessive application of alkaline activators will produce alkali-aggregate reaction, resulting in changes in the structure and volume of the steel slag, reduced durability and strength, and inability to repair. Therefore, at this stage, there is an urgent need for a steel slag activator with good activating effect and no alkali-aggregate reaction. Summary of the invention
[0004] The purpose of the present invention is to provide a composite steel slag activator modified steel slag material and a preparation method thereof, by preparing a corrosion resistance enhancer and adding it to the composite steel slag activator to improve the alkali resistance of the steel slag to solve the problem of alkali aggregate reaction caused by the application of steel slag activator mentioned in the above background technology.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A composite steel slag activator modified steel slag material is composed of the following raw materials in parts by mass: 86-93 parts of steel slag, 4-7 parts of desulfurized gypsum, 1-2 parts of sodium silicate, 0.2-0.4 parts of polyol amine, 0.5-1 parts of polyol, 0.2-0.5 parts of calcium dihydrogen phosphate, and 0.1-0.3 parts of corrosion resistance enhancer.
[0007] A method for preparing a composite steel slag activator modified steel slag material comprises the following steps:
[0008] Step 1: weigh the raw materials by mass: 86-93 parts of steel slag, 4-7 parts of desulfurized gypsum, 1-2 parts of sodium silicate, 0.2-0.4 parts of polyol amine, 0.5-1 parts of polyol, 0.2-0.5 parts of calcium dihydrogen phosphate, and 0.1-0.3 parts of corrosion resistance enhancer;
[0009] Step 2: The raw materials weighed in the first step are mixed evenly and added into a ball mill for ball milling. After the grinding is completed, a composite steel slag activator is obtained;
[0010] Step 3: Add the composite steel slag activator in the second step to the steel slag, mix well and then add to a ball mill for ball milling. After the ball milling is completed, dry to obtain a composite steel slag activator modified steel slag material.
[0011] Furthermore, the polyol amine is one of triethanolamine, diisopropanolamine and triisopropanolamine.
[0012] Furthermore, the polyol is propylene glycol or glycerol.
[0013] Furthermore, in the second step, the ball milling speed is 100-200 r / min, and the ball milling time is 5-15 min.
[0014] Furthermore, in the third step, the rotation speed of the ball milling is 30-40 r / min, and the time of the ball milling is 10-20 min.
[0015] Furthermore, the drying temperature in the third step is 40-50°C.
[0016] Furthermore, the corrosion resistance enhancer is prepared by the following steps:
[0017] Step 1: 4-amino-1,8-naphthalene dicarboxylic anhydride and deionized water are mixed in a three-necked flask, a condenser is installed, magnetic stirring is turned on, and the pH of the system is adjusted to 2 with hydrochloric acid. Then, ammonium thiocyanate is added to the three-necked flask, and the reaction is carried out at a temperature of 100° C. for 10-12 hours. After the reaction is completed, deionized water is added to the three-necked flask for washing, and the mixture is filtered under reduced pressure and dried to obtain intermediate 1;
[0018] Step 2: Add concentrated sulfuric acid to a three-necked flask, install a condenser and a thermometer, turn on magnetic stirring, add intermediate 1 and hydrogen bromide to the three-necked flask at a temperature of 40°C, and then react at a temperature of 65°C for 12 hours. After the reaction is completed, add ice water to the three-necked flask, filter under reduced pressure, and wash the obtained solid with deionized water to obtain intermediate 2;
[0019] Step 3: Mix the intermediate 2, triethylamine and trifluoroacetyl chloride in a chloroform solution in a flask, start magnetic stirring, and react in an ice-water bath for 5 hours. After the reaction is completed, add deionized water to the container for washing, separate the organic layer with a separatory funnel, and rotary evaporate to obtain the intermediate 3;
[0020] Step 4: Mix the intermediate 3, tetrabutylammonium bromide, 2,2,2-trifluoroethylamine and tetrahydrofuran in a three-necked flask, install a condenser and a thermometer, start magnetic stirring, and react at a temperature of 110° C. for 12-14 hours. After the reaction is completed, add ether to the three-necked flask, vacuum filter, and recrystallize the obtained solid to obtain the corrosion resistance enhancer;
[0021] Furthermore, the dosage ratio of 4-amino-1,8-naphthalene dicarboxylic anhydride, deionized water and ammonium thiocyanate used in step 1 is 0.1 mol: 24-30 mL: 0.1-0.12 mol.
[0022] Furthermore, the concentrated sulfuric acid in step 2 is a sulfuric acid aqueous solution with a mass fraction of 98%, and the amount ratio of the concentrated sulfuric acid, intermediate 1, and hydrogen bromide used is 52-60g: 0.09mol: 0.01-0.02mol.
[0023] Furthermore, the chloroform solution of trifluoroacetyl chloride in step 3 is prepared from 0.1 mol of trifluoroacetyl chloride and 80 mL of chloroform, and the amount ratio of the intermediate 2, triethylamine, and the chloroform solution of trifluoroacetyl chloride used is 0.08 mol: 0.06-0.08 mol: 131.6 g.
[0024] Furthermore, the amount ratio of intermediate 3, tetrabutylammonium bromide, 2,2,2-trifluoroethylamine and tetrahydrofuran used in step 4 is 0.06 mol: 5-8 g: 0.07-0.09 mol: 80-100 mL.
[0025] Beneficial effects of the present invention:
[0026] (1) The present invention uses steel slag, desulfurized gypsum, sodium silicate, polyol amine, polyol, calcium dihydrogen phosphate, and corrosion resistance enhancer as raw materials to prepare a composite steel slag activator modified steel slag material. The raw materials used in the present invention are low in cost, non-toxic, harmless, safe and environmentally friendly.
[0027] (2) The present invention uses 4-amino-1,8-naphthalene dicarboxylic anhydride and ammonium thiocyanate as raw materials, obtains intermediate 1 through aqueous thiocyanation, and then oxidizes intermediate 1 under the catalysis of concentrated sulfuric acid and hydrogen bromide to obtain intermediate 2, and then causes the amino group of intermediate 2 to undergo an amidation reaction with the acyl group of trifluoroacetyl chloride to obtain intermediate 3, and finally causes the anhydride part of intermediate 3 to undergo an amidation reaction with 2,2,2-trifluoroethylamine under the catalytic action of phase transfer catalyst tetrabutylammonium bromide to obtain a corrosion resistance enhancer; the corrosion resistance enhancer of the present invention has a naphthoheterocyclic structure and a large cohesive energy, and therefore has good thermal stability. In addition, the corrosion resistance enhancer of the present invention also has a long chain connecting The thiazole structure has good alkali resistance. Moreover, the corrosion-resistant enhancer of the present invention also has a large number of carbon-fluorine bonds at both ends. The carbon-fluorine bonds have large bond energy and good stability. They have good stability in both acid and alkali, which gives the corrosion-resistant enhancer of the present invention good alkali resistance and reduces the hazards such as alkali-aggregate reaction that may be caused by the action of the slag activator. In addition, the corrosion-resistant enhancer of the present invention also has a thiazole structure with good reactivity at one end, and its sulfur atom and nitrogen atom each have a pair of lone pairs of electrons. These lone pairs of electrons can form stable complexes with metal ions in the slag, thereby achieving the purpose of enhancing the excitation effect of the slag activator and enhancing the compatibility of the corrosion-resistant enhancer of the present invention with the slag material.
[0028] (3) The composite steel slag activator prepared in the composite steel slag activator modified steel slag material of the present invention is weakly alkaline as a whole, and the corrosion resistance enhancer in the composite steel slag activator can also improve the alkali resistance of the steel slag material. Therefore, the application of the steel slag activator of the present invention will not produce alkali aggregate effect; not only that, the composite steel slag activator in the composite steel slag activator modified steel slag material of the present invention has a good activating effect on the steel slag material, and the steel slag material after activation has high compressive strength and good stability. DETAILED DESCRIPTION
[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1
[0030] A corrosion resistance enhancer comprises the following preparation steps:
[0031] Step 1: 0.1 mol 4-amino-1,8-naphthalene dicarboxylic anhydride and 24 mL deionized water were mixed in a container, stirred evenly, and the pH of the system was adjusted to 2 with hydrochloric acid, and then 0.1 mol ammonium thiocyanate was added to the container, and the reaction was carried out at a temperature of 100°C for 10 hours. After the reaction was completed, deionized water was added to the container for washing, and the intermediate 1 was obtained after vacuum filtration and drying;
[0032] Step 2: Add 52 g of 98% sulfuric acid aqueous solution into a container, stir evenly, add 0.09 mol of intermediate 1 and 0.01 mol of hydrogen bromide into the container at 40°C, and then react for 12 hours at 65°C. After the reaction, add ice water into the container, filter under reduced pressure, and wash the obtained solid with deionized water to obtain intermediate 2;
[0033] Step 3: 0.08 mol of intermediate 2, 0.06 mol of triethylamine, and 131.6 g of a chloroform solution of trifluoroacetyl chloride were mixed in a container, stirred evenly, and reacted in an ice-water bath for 5 h. After the reaction was completed, deionized water was added to the container for washing, and the organic layer was separated and rotary evaporated to obtain intermediate 3. The chloroform solution of trifluoroacetyl chloride used in this step was prepared from 0.1 mol of trifluoroacetyl chloride and 80 mL of chloroform;
[0034] Step 4: 0.06 mol of intermediate 3, 5 g of tetrabutylammonium bromide, 0.07 mol of 2,2,2-trifluoroethylamine and 80 mL of tetrahydrofuran are mixed in a container, stirred evenly, and reacted at 110° C. for 12 h. After the reaction, ether is added to the container, vacuum filtered, and the obtained solid is recrystallized to obtain the corrosion resistance enhancer. Example 2
[0035] A corrosion resistance enhancer comprises the following preparation steps:
[0036] Step 1: 0.1 mol 4-amino-1,8-naphthalene dicarboxylic anhydride and 27 mL deionized water were mixed in a container, stirred evenly, and the pH of the system was adjusted to 2 with hydrochloric acid, and then 0.11 mol ammonium thiocyanate was added to the container, and the reaction was carried out at a temperature of 100°C for 11 hours. After the reaction was completed, deionized water was added to the container for washing, and the intermediate 1 was obtained after vacuum filtration and drying;
[0037] Step 2: Add 56 g of 98% sulfuric acid aqueous solution into a container, stir evenly, add 0.09 mol of intermediate 1 and 0.015 mol of hydrogen bromide into the container at 40°C, and then react for 12 hours at 65°C. After the reaction is completed, add ice water into the container, filter under reduced pressure, and wash the obtained solid with deionized water to obtain intermediate 2;
[0038] Step 3: 0.08 mol of intermediate 2, 0.07 mol of triethylamine, and 131.6 g of a chloroform solution of trifluoroacetyl chloride were mixed in a container, stirred evenly, and reacted in an ice-water bath for 5 h. After the reaction was completed, deionized water was added to the container for washing, and the organic layer was separated and rotary evaporated to obtain intermediate 3. The chloroform solution of trifluoroacetyl chloride used in this step was prepared from 0.1 mol of trifluoroacetyl chloride and 80 mL of chloroform;
[0039] Step 4: 0.06 mol of intermediate 3, 7 g of tetrabutylammonium bromide, 0.08 mol of 2,2,2-trifluoroethylamine and 90 mL of tetrahydrofuran are mixed in a container, stirred evenly, and reacted at 110° C. for 13 h. After the reaction, ether is added to the container, vacuum filtered, and the obtained solid is recrystallized to obtain the corrosion resistance enhancer. Example 3
[0040] A corrosion resistance enhancer comprises the following preparation steps:
[0041] Step 1: 0.1 mol 4-amino-1,8-naphthalene dicarboxylic anhydride and 30 mL deionized water were mixed in a container, stirred evenly, and the pH of the system was adjusted to 2 with hydrochloric acid, and then 0.12 mol ammonium thiocyanate was added to the container, and the reaction was carried out at a temperature of 100°C for 12 hours. After the reaction was completed, deionized water was added to the container for washing, and the intermediate 1 was obtained after vacuum filtration and drying;
[0042] Step 2: Add 60 g of 98% sulfuric acid aqueous solution into a container, stir evenly, then add 0.09 mol of intermediate 1 and 0.02 mol of hydrogen bromide into the container at 40°C, and then react for 12 hours at 65°C. After the reaction is completed, add ice water into the container, filter under reduced pressure, and wash the obtained solid with deionized water to obtain intermediate 2;
[0043] Step 3: 0.08 mol of intermediate 2, 0.08 mol of triethylamine, and 131.6 g of a chloroform solution of trifluoroacetyl chloride were mixed in a container, stirred evenly, and reacted in an ice-water bath for 5 h. After the reaction was completed, deionized water was added to the container for washing, and the organic layer was separated and rotary evaporated to obtain intermediate 3. The chloroform solution of trifluoroacetyl chloride used in this step was prepared from 0.1 mol of trifluoroacetyl chloride and 80 mL of chloroform;
[0044] Step 4: 0.06 mol of intermediate 3, 8 g of tetrabutylammonium bromide, 0.09 mol of 2,2,2-trifluoroethylamine and 100 mL of tetrahydrofuran are mixed in a container, stirred evenly, and reacted at 110° C. for 14 h. After the reaction, ether is added to the container, vacuum filtered, and the obtained solid is recrystallized to obtain the corrosion resistance enhancer. Example 4
[0045] A composite steel slag activator modified steel slag material is composed of the following raw materials in parts by mass: 86 parts of steel slag, 4 parts of desulfurized gypsum, 1 part of sodium silicate, 0.2 parts of triethanolamine, 0.5 parts of propylene glycol, 0.2 parts of calcium dihydrogen phosphate, and 0.1 parts of the corrosion resistance enhancer obtained in Example 1.
[0046] A method for preparing a composite steel slag activator modified steel slag material comprises the following steps:
[0047] Step 1: Weigh the raw materials by mass: 86 parts of steel slag, 4 parts of desulfurized gypsum, 1 part of sodium silicate, 0.2 parts of triethanolamine, 0.5 parts of glycerol, 0.2 parts of monocalcium phosphate, and 0.1 parts of the corrosion-resistant enhancer obtained in Example 1;
[0048] Step 2: The raw materials weighed in the first step are mixed evenly and added into a ball mill for ball milling at a speed of 100 r / min for 5 minutes. After the running-in is completed, a composite steel slag activator is obtained;
[0049] Step 3: Add the composite steel slag activator in the second step to the steel slag, mix well and add into a ball mill for ball milling at a speed of 30r / min for 10 minutes. After ball milling, dry at a temperature of 40°C to obtain a composite steel slag activator modified steel slag material. Example 5
[0050] A composite steel slag activator modified steel slag material is composed of the following raw materials in parts by mass: 86 parts of steel slag, 4 parts of desulfurized gypsum, 1 part of sodium silicate, 0.4 parts of diisopropanolamine, 1 part of propylene glycol, 0.5 parts of calcium dihydrogen phosphate, and 0.3 parts of the corrosion resistance enhancer obtained in Example 2.
[0051] A method for preparing a composite steel slag activator modified steel slag material comprises the following steps:
[0052] Step 1: Weigh the raw materials by mass: 86 parts of steel slag, 4 parts of desulfurized gypsum, 1 part of sodium silicate, 0.4 parts of diisopropanolamine, 1 part of propylene glycol, 0.5 parts of monocalcium phosphate, and 0.3 parts of the corrosion-resistant enhancer obtained in Example 2;
[0053] Step 2: The raw materials weighed in the first step are mixed evenly and added into a ball mill for ball milling at a speed of 150 r / min for 10 minutes. After the running-in is completed, a composite steel slag activator is obtained;
[0054] Step 3: Add the composite steel slag activator in the second step to the steel slag, mix well and add into the ball mill for ball milling at a speed of 35r / min for 15 minutes. After ball milling, dry at a temperature of 45°C to obtain a composite steel slag activator modified steel slag material. Example 6
[0055] A composite steel slag activator modified steel slag material is composed of the following raw materials in parts by mass: 93 parts of steel slag, 7 parts of desulfurized gypsum, 2 parts of sodium silicate, 0.2 parts of triisopropanolamine, 0.5 parts of glycerol, 0.2 parts of calcium dihydrogen phosphate, and 0.1 parts of the corrosion resistance enhancer obtained in Example 3.
[0056] A method for preparing a composite steel slag activator modified steel slag material comprises the following steps:
[0057] Step 1: weigh the raw materials by mass: 93 parts of steel slag, 7 parts of desulfurized gypsum, 2 parts of sodium silicate, 0.2 parts of triisopropanolamine, 0.5 parts of glycerol, 0.2 parts of monocalcium phosphate, and 0.1 parts of the corrosion-resistant enhancer obtained in Example 3;
[0058] Step 2: The raw materials weighed in the first step are mixed evenly and added into a ball mill for ball milling at a speed of 200 r / min for 15 minutes. After the running-in is completed, a composite steel slag activator is obtained;
[0059] Step 3: Add the composite steel slag activator in the second step to the steel slag, mix well and add into a ball mill for ball milling at a speed of 40r / min for 20 minutes. After ball milling, dry at a temperature of 50°C to obtain a composite steel slag activator modified steel slag material.
[0060] Comparative Example 1
[0061] The "corrosion resistance enhancer obtained in Example 3" used in Example 6 was removed, and the other conditions remained unchanged.
[0062] Comparative Example 2
[0063] This comparative example is the Ramans steel slag activator sold by Liaocheng Jiukun Building Materials Co., Ltd.
[0064] The Ramanse slag activator sold by Liaocheng Jiukun Building Materials Co., Ltd. was added to the steel slag at a dosage of 10% of the mass fraction of the steel slag. After uniform mixing, the mixture was added to a ball mill and milled at a speed of 40r / min for 20 minutes. After the ball milling was completed, the mixture was dried at a temperature of 50°C to obtain a Ramanse slag activator modified steel slag material.
[0065] The composite steel slag activator modified steel slag material obtained in Examples 4-6 and Comparative Example 1 and the Ramans steel slag activator modified steel slag material obtained in Comparative Example 2 were mixed with standard cement at a mass ratio of 3:7, and cured at 20°C for 28 days according to the national standard GB / T17671-1999 test standard, and the compressive strength of each group was tested, and the stability of each group was tested according to the Redclamp method of the national standard GB / T1346-2011. The test results are shown in Table 1:
[0066] Table 1
[0067]
[0068] It can be seen from Table 1 that the overall compressive strength and stability of the substrate after the composite steel slag activator modified steel slag material of the present invention is mixed with cement are better than those of the substrate after the commercially available Ramans steel slag activator modified steel slag material is mixed with cement. However, the overall compressive strength and stability of the steel slag material modified by the composite steel slag activator in Comparative Example 1 are not good after mixing with cement. This may be due to the fact that the corrosion-resistant enhancer of the present invention is not added, resulting in the alkali-aggregate reaction of the concrete affected by the alkalinity of the steel slag activator, resulting in strength loss and volume expansion. Combined with Table 1 as a whole, it can be concluded that the corrosion-resistant enhancer of the present invention has a good stimulating effect on the modified steel slag material used in the steel slag activator, and will not cause the alkali-aggregate reaction to affect the performance of the substrate.
[0069] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A composite steel slag activator modified steel slag material, composed of the following raw materials in parts by weight: 86-93 parts of steel slag, 4-7 parts of desulfurized gypsum, 1-2 parts of sodium silicate, 0.2-0.4 parts of polyol amine, 0.5-1 parts of polyol, 0.2-0.5 parts of calcium dihydrogen phosphate, 0.1-0.3 parts of corrosion resistance enhancer; Wherein, the corrosion resistance enhancer is prepared by the following steps: Step 1: 0.1 mol 4-amino-1,8-naphthalene dicarboxylic anhydride and 24-30 mL deionized water are mixed in a container, stirred evenly, and the pH of the system is adjusted to 2 with hydrochloric acid, and then 0.1-0.12 mol ammonium thiocyanate is added to the container, and the reaction is carried out at a temperature of 100° C. for 10-12 hours to obtain intermediate 1; Step 2: Add 52-60 g of concentrated sulfuric acid into a container, add 0.09 mol of intermediate 1 and 0.01-0.02 mol of hydrogen bromide into the container at a temperature of 40° C., and then react at a temperature of 65° C. for 12 hours to obtain intermediate 2; Step 3: 0.08 mol of intermediate 2, 0.06-0.08 mol of triethylamine, and 131.6 g of a solution prepared by 0.1 mol of trifluoroacetyl chloride and 80 mL of chloroform were mixed in a container, stirred evenly, and reacted in an ice-water bath for 5 h to obtain intermediate 3; Step 4: 0.06 mol of intermediate 3, 5-8 g of tetrabutylammonium bromide, 0.07-0.09 mol of 2,2,2-trifluoroethylamine, and 80-100 mL of tetrahydrofuran are mixed in a container, stirred evenly, and reacted at 110° C. for 12-14 h to obtain the corrosion resistance enhancer.
2. A method for preparing the composite steel slag activator modified steel slag material as claimed in claim 1, characterized in that: The following steps are involved: Step 1: weigh the raw materials by mass: 86-93 parts of steel slag, 4-7 parts of desulfurized gypsum, 1-2 parts of sodium silicate, 0.2-0.4 parts of polyol amine, 0.5-1 parts of polyol, 0.2-0.5 parts of calcium dihydrogen phosphate, and 0.1-0.3 parts of corrosion resistance enhancer; Step 2: The raw materials weighed in the first step are mixed evenly and added into a ball mill for ball milling. After the grinding is completed, a composite steel slag activator is obtained; Step 3: Add the composite steel slag activator in the second step to the steel slag, mix well and then add to a ball mill for ball milling. After the ball milling is completed, dry to obtain a composite steel slag activator modified steel slag material.
3. The method for preparing a composite steel slag activator modified steel slag material according to claim 2, characterized in that: The polyol amine is one of triethanolamine, diisopropanolamine and triisopropanolamine.
4. The method for preparing a composite steel slag activator modified steel slag material according to claim 2, characterized in that: The polyol is propylene glycol or glycerol.
5. The method for preparing a composite steel slag activator modified steel slag material according to claim 2, characterized in that: In the second step, the ball milling speed is 100-200 r / min and the ball milling time is 5-15 min.
6. The method for preparing a composite steel slag activator modified steel slag material according to claim 2, characterized in that: In the third step, the ball milling speed condition is 30-40r / min, the ball milling time condition is 10-20min, and the drying temperature condition is 40-50°C.
Citation Information
Patent Citations
Composite steel slag activator, modified steel slag material containing composite steel slag activator and preparation method thereof
CN112723789A
High-performance concrete with large mixing amount of undisturbed red mud and preparation process of high-performance concrete
CN115490470A